2008
DOI: 10.1097/mnm.0b013e3282f3d052
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of bone SPECT to the diagnosis of bone metastases in an African population

Abstract: In a setting where SPECT is not easily available, planar imaging alone is still adequate in the vast majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results from prospective trials might not be applicable to clinical routine, because these trials included highly selected patient collectives which are not representative for everyday clinical routine. Only few studies have evaluated the value of additional SPECT in unselected patients from clinical routine [3][4][5][6][7][8][9][10][11], all of them with rather small sample sizes. Some of these studies reported the fraction of lesions missed in planar images but detected by SPECT to be significant (20.1-25.6%) [5,6], while other authors found this fraction to be rather small (4.3%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results from prospective trials might not be applicable to clinical routine, because these trials included highly selected patient collectives which are not representative for everyday clinical routine. Only few studies have evaluated the value of additional SPECT in unselected patients from clinical routine [3][4][5][6][7][8][9][10][11], all of them with rather small sample sizes. Some of these studies reported the fraction of lesions missed in planar images but detected by SPECT to be significant (20.1-25.6%) [5,6], while other authors found this fraction to be rather small (4.3%) [7].…”
Section: Introductionmentioning
confidence: 99%